Reduced mammalian target of rapamycin activity facilitates mitochondrial retrograde signaling and increases life span in normal human fibroblasts. Issue 6 (30th July 2013) - Lerner, Chad; Bitto, Alessandro; Pulliam, Daniel; Nacarelli, Timothy; Konigsberg, Mina; Van, Holly; Torres, Claudio; Sell, Christian
Summary Coordinated expression of mitochondrial and nuclear genes is required to maintain proper mitochondrial function. However, the precise mechanisms that ensure this coordination are not well defined. We find that signaling from mitochondria to the nucleus is influenced by mammalian target of rapamycin (mTOR) activity via changes in autophagy and p62/SQSTM1 turnover. Reducing mTOR activity increases autophagic flux, enhances mitochondrial membrane potential, reduces reactive oxygen species within the cell, and increases replicative life span. These effects appear to be mediated in part by an interaction between p62/SQSTM1 and Keap1. This interaction allows nuclear accumulation of the nuclear factor erythroid 2‐like 2 (NFE2L2, also known as nuclear factor related factor 2 or NRF2), increased expression of the nuclear respiratory factor 1 (NRF1), and increased expression of nuclear‐encoded mitochondrial genes, such as the mitochondrial transcription factor A, and mitochondrial‐encoded genes involved in oxidative phosphorylation. These findings reveal a portion of the intracellular signaling network that couples mitochondrial turnover with mitochondrial renewal to maintain homeostasis within the cell and suggest mechanisms whereby a reduction in mTOR activity may enhance longevity.